2022
DOI: 10.1061/(asce)em.1943-7889.0002132
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Microcracked Porous Solids: Modeling from Homogenization to Percolation

Abstract: This paper establishes a comprehensive modeling for permeability of porous solids incorporating cracks with clustering extent ranging from nonoverlapping to percolation. The geometry of cracks is characterized through the crack density, orientation, connectivity, and fractal dimension of crack networks. The interaction direct derivative (IDD) model from effective medium theory is developed to predict the permeability of solids with nonoverlapping cracks and further extended by a two-step scheme to account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…[30], © Elsevier Ltd., 2012; (c) four-point bending method [32,33], reproduced with permission from Ref. [32], © ASCE, 2011; (d) center expansion method [27]; (e) splitting method [4,24]; and (f) Wedge splitting method [34,35], reproduced with permission from Ref. [34], © RILEM, 2007.…”
Section: Many Scholars Have Conducted Experimental Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…[30], © Elsevier Ltd., 2012; (c) four-point bending method [32,33], reproduced with permission from Ref. [32], © ASCE, 2011; (d) center expansion method [27]; (e) splitting method [4,24]; and (f) Wedge splitting method [34,35], reproduced with permission from Ref. [34], © RILEM, 2007.…”
Section: Many Scholars Have Conducted Experimental Researchmentioning
confidence: 99%
“…Due to differences in concrete materials and testing equipment, the compressive stress thresholds obtained by different scholars are not consistent, ranging from 30% to 70%. For prestressed concrete members, the permeability coefficient of chloride ions decreases with increasing pressure when the construction load is less than 55% of the compressive strength (f c ) of the concrete [24]. Picandet et al [42] observed the permeability of concrete by unloading concrete specimens subjected to axial compressive loads, and the experimental results showed that the permeability of concrete would increase significantly when the stress level reached 90% of the ultimate strength.…”
Section: Compression Stress Conditionmentioning
confidence: 99%
See 2 more Smart Citations